The complete mitochondrial genome of Setaria labiatepapillosa (Spirurida: Setariidae). Issue 1 (2nd January 2019) - Gao, Jun-Feng; Hou, Mei-Ru; Cui, Yu-Chao; Shi, Tong-Rui
Abstract: The complete mitochondrial genome of Setaria labiatepapillosa is reported for the first time in this study. Its entire mitogenome is 13, 950 bp in length, contained 12 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and one noncoding regions. Arrangement of the 12 PCGs was identical to that of most filaria mtDNA sequence. The phylogenetic analyses by Bayesian inference method revealed that S. labiatepapillosa and S. digitata belong to Setariidae are in the same clade with strong support, the result supports classical taxonomic of the filariae. The mtDNA dataset provide a novel genetic marker for further studies of filaria.